PENGARUH PELATIHAN PENGAWASAN KERJA DAN KETERAMPILAN KERJA TERHADAP KINERJA KARYAWAN PT SIIX ELECTRONICS INDONESIA - Situmorang, Mitra Ronia; Hikmah (SCIENTIA JOURNAL, 2021)
ABSTRACTIn the current era of globalization, every organization or company competes with each other to show the advantages of their respective companies. Competition that is constantly evolving at this time requires organization to be able to survive in the existing rivalry, as well as develop every quality human resource. The organization will endeavor to expand representatives to acquire advantages and an incentive for the organization, in order to work on the government assistance of proprietors and employeesThe reason for this examination is to examine the impact of preparing, job supervision and job skills at the same time on worker execution at PT Siix Electronics Indonesia Batam. The populace in this examination were operator of departement production SMT line 9A PT Siix Electronics Indonesia Batam. The quantity of tests in this investigation was 100 utilizing non propobability examining method. The results showed, among others:training partially have positive and significative influence on worker presentment; job supervision partially have substantial and significant on worker presentment ;job skills of work partially dosen’t have positive and substantial impact on worker presentment; showing that of training, job supervision furthermore, work abilities all the while have positive and huge influence representative execution.Keywords: Employee Performance; Job Skills; Training, Job Supervision.